Analisis Keterampilan Berbicara Siswa dalam Mata Pelajaran Bahasa Indonesia Kelas IV Sekolah Dasar - Delmawita, Delmawita; Latif, Latif (Cetta: Jurnal Ilmu Pendidikan, 2025)
Speaking skills are a crucial aspect in shaping a generation that is intelligent, innovative, and cultured. However, various issues are still found in students’ speaking abilities at SDN 48 Pekanbaru, particularly among fourth-grade students. This study aims to describe the speaking skills of fourth-grade students in the Indonesian language subject at SDN 48 Pekanbaru. The research employed a qualitative approach with a descriptive method. The subjects of the study consisted of students and the fourth-grade homeroom teacher. Data collection techniques included interviews, observations, and documentation, using instruments such as interview guides, observation sheets, and document analysis forms. The data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that the speaking skills of fourth-grade students remain at a moderate to low level across various indicators. Students experienced difficulties such as inaccurate pronunciation, inappropriate use of volume and intonation, disorganized sentence construction, and inability to express ideas in their own words. Factors such as shyness, nervousness, and low self-confidence were identified as major obstacles to students' speaking proficiency. Nevertheless, some students have shown relatively good speaking abilities, particularly in terms of fluency and expression.